Local Area Network (LAN) Design And Simulation Using Cisco Packet Tracer - Putri, Candani; Ali Amran; Istnan Mubarok; Serlin Nurfita Sari; Novi Anti I.P.N.C (Cattleya Darmaya Fortuna, 2024)
Computer networks need to be managed well so that traffic on the network becomes more efficient. One of the layers of computer network management is the router device. This research uses Cisco Packet Tracer software. Cisco Packet Tracer is a network simulation tool for understanding, designing, and testing computer networks. It is a very popular tool among students, networking educators, and IT professionals for training and demonstrating networking concepts. The aim of this research is to analyze and design a LAN network with a tree topology. The simulation test results show that in each router in a different room during the data sending process there are no lost packets.